Causality between Financial Development and Economic Growth in Nepal - Maharjan, Rajendra (NRB Economic Review, 2020)
This study examines the empirical relationship between financial development and economic growth in Nepal. Financial development has been measured by three key pillars of the financial system bank, capital market and insurance. Gross domestic product and gross fixed capital formation are considered for economic growth indicators. Using time series techniques, the stationary properties of the data sets are tested followed by Johansen co-integration test to observe long run equilibrium relationship between the two variables and Granger Causality test to identify the causal relationship among the variables. Also, Vector Error Correction Model (VECM) has been employed to analyze the short run dynamics of the system. The result of the study reveals that there is cointegrating relationship between market capitalization and economic development with short-run causality is running from market capitalization to GDP. In regard to insurance market, error correction term is negative and significance for both GDP and GCF indicating there is cointegrating relationship between insurance market and economic development. However, the result shows no evidence of causality between insurance premium and economic development in short-run. The negative relation between bank and GDP reinforces that there is a cointegrating relationship between banking sector development and economic development. The result also shows that lagged value of GDP is significant. It shows that short-run causality is running from GDP to banking sector development.Nepal